Master tracks in different resolutions during POLAR 5 campaign P5_238_ANTSI_2022 - Haas, Christian (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2023)
Raw data acquired by GPS1 position sensors on board research aircraft Polar 5 during the campaign P5_238_ANTSI_2022 were processed to receive a validated master track which can be used as reference of further expedition data. Novatel FlexPak6 GPS receiver was used as navigation sensors during the campaign. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) with a resolution of 1 sec. Processed data are provided as a master track with 1 sec resolution and a generalized track with a reduced set of the most significant positions of the master track. A detailed report on processing is also available for each flight.